Crystal structures of substrate‐bound chitinase from the psychrophilic bacterium Moritella marina and its structure in solution. (1st March 2014) - Malecki, Piotr H.; Vorgias, Constantinos E.; Petoukhov, Maxim V.; Svergun, Dmitri I.; Rypniewski, Wojciech
<x xml:space="preserve">Abstract</x> The four‐domain structure of chitinase 60 from Moritella marina (MmChi60) is outstanding in its complexity. Many glycoside hydrolases, such as chitinases and cellulases, have multi‐domain structures, but only a few have been solved. The flexibility of the hinge regions between the domains apparently makes these proteins difficult to crystallize. The analysis of an active‐site mutant of MmChi60 in an unliganded form and in complex with the substrates NAG4 and NAG5 revealed significant differences in the substrate‐binding site compared with the previously determined complexes of most studied chitinases. A SAXS experiment demonstrated that in addition to the elongated state found in the crystal, the protein can adapt other conformations in solution ranging from fully extended to compact.